PERAN INTELIJEN KEPOLISIAN DALAM PENGUNGKAPAN TINDAK PIDANA PEMBUNUHAN DIKEPOLISIAN RESOR KOTA DENPASAR - Murni, Selfiani Rosdiana; Hengki, I Gusti Bagus (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
Murder is the act of taking another person's life by breaking the law or not breaking the law. Murder is also a heinous act that takes the life of another person intentionally or unintentionally. The purpose of this research was to determine the role of intelligence in disclosing criminal acts of murder and the factors that influence the function of implementing intelligence in the Denpasar City Police Department. The research method used by the author is empirical legal research. The type of approach used is a sociological approach with data collection techniques using observation, interviews and documentation where after the data has been collected it will be analyzed using qualitative methods. The results of this research show that the role of police intelligence in disclosing criminal acts of murder in the Denpasar City Resort Police is really needed by the people of Denpasar City.